Impact of Facilitated Behavior Change Strategies on Food Intake Monitoring and Body Weight Measurements in Acute Care: Case Examples From the More‐2‐Eat Study. (20th November 2018) - Laur, Celia; Butterworth, Donna; Nasser, Roseann; Bell, Jack; Marcell, Chelsa; Murphy, Joseph; Valaitis, Renata; Bernier, Paule; Ray, Sumantra; Keller, Heather
Abstract: Background : Assessing and monitoring food intake and body weight of all hospital patients is considered part of "best practice" nutrition care. This study presents case examples describing the impact of behavior change strategies on embedding these 2 monitoring processes in hospitals. Methods : Four hospital medical units that participated in the More‐2‐Eat implementation study to improve nutrition care focused on improving food intake and/or weight monitoring practices. The percentage of admitted patients who received these care practices were tracked through chart audits over 18 months. Implementation progress and behavior change strategies were documented through interviews, focus groups, scorecards, and monthly telephone calls. Case examples are explored using mixed methods. Results : Of the 4 units, 3 implemented food intake monitoring. One provided food service workers the opportunity to record food intake, with low intake discussed by an interdisciplinary team during bedside rounds (increased from 0% to 97%). Another went from 0% to 61% of patients monitored by introducing a new form ("environmental restructuring") reminding staff to ask patients about low intake. A third unit increased motivation to improve documentation of low intake and improved from 3% to 95%. Two units focused on regularity of body weight measurement. One unit encouraged a team approach and introduced 2 weigh days/week (improved from 14% to 63%), while another increased opportunity by having all patients weighed on Saturdays (improved from 11% to 49%). Conclusion : Difficult‐to‐change nutrition care practices can be implemented using diverse and ongoing behavior change strategies, staff input, a champion, and an interdisciplinary team.